First-principles study of Fe2VAl and Fe2VAl/Si thin films and their magnetic properties. (1st September 2022) - Kobayashi, Kazuaki; Takaki, Hirokazu; Shimono, Masato; Ishii, Hiroyuki; Kobayashi, Nobuhiko; Hirose, Kenji; Tsujii, Naohito; Mori, Takao
Abstract: We studied thin films of Fe2 VAl, Fe2 VAl/Si, and a related compound using the total energy pseudopotential method. The internal atoms in a supercell of the repeated slab model were fully relaxed, except for Fe2 VAl/Si. The detailed electronic and magnetic properties of structurally relaxed thin films of Fe2 VAl, Fe2 VAl/Si, and a related compound were calculated. These films are free-standing in the supercell, except for Fe2 VAl/Si, which comprises Fe2 VAl and Si (substrate) layers in a supercell. A thin film comprising Fe2 V, Al, and Si (substrate) layers in the supercell (denoted as Fe2 V/Al/Si) was also studied. Although electronic states of bulk Fe2 VAl (full-Heusler) are metallic with pseudo-gap states around the Fermi level and nonmagnetic, the calculation results for Fe2 VAl, Fe2 VAl/Si, and Fe2 V/Al/Si thin films in this study indicate that the films have ferromagnetic properties and their ferromagnetic states are energetically more favorable than nonmagnetic states. The magnetic moments are large and enhanced in the thin films. The magnetic moments of Fe in Fe2 VAl (Fe12 V4 Al4 ), Fe2 VAl (Fe20 V8 Al8 ), Fe2 VAl/Si, and Fe2 V/Al/Si thin films are 2.07 μ B /per atom, 1.29 μ B /per atom, 1.83 μ B /per atom, and 2.22 μ B /per atom, respectively. Although thin films have net ferromagnetic properties, the magnetic moments of the up and down spin states of Fe and V are antiferromagnetically aligned.